Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Sistem Persamaan Linier Tiga Variabel (SPLTV) Berdasarkan Prosedur Newman - Hidayanto, Erry; Lisrahmat, Mimin Nazura (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2023)
The purpose of this study was to describe the form of student errors in solving SPLTV story questions based on Newman's procedures and their causes. This research method uses a qualitative approach with a descriptive qualitative research type with the subject of three students of class X a high school in Malang. The forms of errors found in this study were: unable to read the questions carefully, unable to understand the meaning of each important symbol or term contained in the questions; unable to understand the important information contained in the questions, incorrectly in writing the information implied in the questions, not writing down any information either known or asked from the questions; less precise in making illustrations for each variable used, not writing illustrations used for each variable in the equations that have been made, unable to transform the information in the problem into mathematical form correctly and precisely; unable to continue the calculation procedure until the final answer is found, incorrectly in writing the calculation results obtained from the elimination process; did not write the final answer, did not include the units in the final answer, incorrectly wrote the units in the final answer, did not write the conclusion of the final answer according to what was asked or asked for in the question. The causes of these errors: not being careful, in a hurry, not focusing, afraid of running out of time, being careless, and not checking the final answer.